Adipose tissue aging is regulated by an altered immune system - Zhang, Yi-Xiang; Ou, Min-Yi; Yang, Zi-Han; Sun, Yu; Li, Qing-Feng; Zhou, Shuang-Bai (Frontiers in Immunology, 2023)
Adipose tissue is a widely distributed organ that plays a critical role in age-related physiological dysfunctions as an important source of chronic sterile low-grade inflammation. Adipose tissue undergoes diverse changes during aging, including fat depot redistribution, brown and beige fat decrease, functional decline of adipose progenitor and stem cells, senescent cell accumulation, and immune cell dysregulation. Specifically, inflammaging is common in aged adipose tissue. Adipose tissue inflammaging reduces adipose plasticity and pathologically contributes to adipocyte hypertrophy, fibrosis, and ultimately, adipose tissue dysfunction. Adipose tissue inflammaging also contributes to age-related diseases, such as diabetes, cardiovascular disease and cancer. There is an increased infiltration of immune cells into adipose tissue, and these infiltrating immune cells secrete proinflammatory cytokines and chemokines. Several important molecular and signaling pathways mediate the process, including JAK/STAT, NFκB and JNK, etc. The roles of immune cells in aging adipose tissue are complex, and the underlying mechanisms remain largely unclear. In this review, we summarize the consequences and causes of inflammaging in adipose tissue. We further outline the cellular/molecular mechanisms of adipose tissue inflammaging and propose potential therapeutic targets to alleviate age-related problems.